Blended learning in higher education: Students’ perceptions and their relation to outcomes - López-Pérez, M. Victoria; Pérez-López, M. Carmen; Rodríguez-Ariza, Lázaro (Computers and education, 2011)
New information and communication technologies (ICTs) provide educators and learners with an innovative learning environment to stimulate and enhance the teaching and learning process. In this context, novel educational concepts such as blended learning are being developed. In the present paper, we present the results obtained from a blended learning experience carried out at the University of Granada. A total of 17 groups took part, with 1431 students registered for the 2009–2010 academic year. In this study, we use objective outcomes and the students’ perceptions regarding the blended learning activities performed. The study shows that the use of blended learning has a positive effect in reducing dropout rates and in improving exam marks. Moreover, the students’ perceptions on blended learning are interrelated, with their final marks depending on the blended learning activities, and on the students’ age, background and class attendance rate.